Isolation and genome sequencing of Staphylococcus schleiferi subspecies coagulans from Antarctic and North Sea seals. Issue 10 (21st October 2020) - Foster, Geoff; Robb, Andrew; Paterson, Gavin K.
Abstract : Reports on the commensal organism and opportunistic pathogen Staphylococcus schleiferi have largely considered isolates from humans and companion dogs. Two subspecies are recognized: the coagulase-negative S. schleiferi ssp. schleiferi, typically seen in humans, and the coagulase-positive S. schleiferi ssp. coagulans, typically seen in dogs. In this study, we report the isolation, genome sequencing and comparative genomics of three S. schleiferi ssp. coagulans isolates from mouth samples from two species of healthy, free-living Antarctic seals, southern elephant seals ( Mirounga leonina ) and Antarctic fur seals ( Arctocephalus gazella ), in the South Orkney Islands, Antarctica, and three isolates from post-mortem samples from grey seals ( Halichoerus grypus ) in Scotland, UK. This is the first report of S. schleiferi ssp. coagulans isolation from Antarctic fur seal and grey seal. The Antarctic fur seal represents the first isolation of S. schleiferi ssp. coagulans from the family Otariidae, while the grey seal represents the first isolation from a pinniped in the Northern Hemisphere. We compare seal, dog and human isolates from both S. schleiferi subspecies in the first genome-based phylogenetic analysis of the species.